Android-Based E-Learning Application Design in Schools - Iskandar, Akbar; Mansyur, Mansyur; Ansari Saleh Ahmar; Muliadi, Muliadi; Abdul Rahman (PT Mattawang Mediatama Solution, 2023)
The concept of E-Learning itself is a guide between learning processes that are packaged in the form of information technology. During the pandemic, schools in Indonesia began to make changes to offline learning to online by utilizing various applications such as the Google Classroom and WhatsApp applications. Based on these conditions, the researcher tried to develop a system for use in schools in the form of Android-based e-learning using the waterfall method. Based on the results of system design and testing it appears that this system can be used at research locations because the system can run well based on the results of black box testing, while the expert judgment of 10 people said it was very good, while the user response was 150 people with a very good response of 70 percent (105 people), good 30 percent (45 people). So that by using an Android-based E-Learning application, of course learning done in schools is better than those that only use conventional models or only use Whatsapp or Google Classroom. In addition, with E-Learning the learning process that is usually carried out in schools can be done without having to go to school again, students and teachers can carry out the learning process from their respective homes using smartphones and the internet.